Analisis Perubahan Vegetasi Untuk Indentifikasi Wilayah Di Kabupaten Sukoharjo Menggunakan Normalized Difference Vegetation Index - Aji Sudrajat, Ilham; Hasbi, Muhammad; Laksito Yuli Saptomo, Wawan; Widada, Bebas; Kusumaningrum, Andriani (Journal of Information Technology, Computer Engineering and Artificial Intelligence (ITCEA), 2026)
This study aims to analyze the changes in vegetation density in Sukoharjo Regency over the past five years using the NDVI method. This research was conducted due to the rapid rate of land use change triggered by the rapid population growth from year to year as it is currently, causing a rapid rate of land use change in Sukoharjo Regency. Previous studies have shown that, increasing land-use change without considering green open space will have a very negative impact on the environment in the area. Geographic Information Systems are needed to see the type of vegetation in the research area, the NDVI method is used because this method provides simplicity to be a starting point in analyzing vegetation and is very suitable for use for long-term temporal data comparison. The research findings reveal a substantial change in land use over the past five years, with an increase of 749.28 hectares or 15.24% from the baseline year of 2020 to 2024. The results of this analysis provide important information for the public works and spatial planning department, as it can be used as input in conducting regional spatial planning and environmental management in the future.